The Effect of Applying Peer Assist Model on Clinical Performance of Nursing Students - Pourgholam, Nima; Poortaghi, Sarieh; tajalli, Saleheh; Ashghali Farahani, Mansoureh; Azami, Masoomeh (Advances in Nursing & Midwifery, 2023)
Introduction: Clinical educations are the most important part of nursing education. One of the ways to develop the clinical performance of nursing students is to use the Peer Assist Model. Therefore, this study was conducted to determine the effect of using the Peer Assist Model on the clinical performance of nursing students. Methods: The present study is experimental which was conducted in 2019-2021. The study population consisted of nursing students of the seventh and eighth semesters of undergraduate nursing and midwifery schools in Iran medical science universities. The samples were 160 students who were randomly assigned to intervention and control groups. At the end of the first day of the internship, the students who had the highest performance appraisal score were selected and after 6 hours of teaching the principles of peer review, they acted as peers in the following days, respectively. Data collection tools included demographic questionnaire that is nursing students’ performance scale with 28-item that was designed by Karayurt et al. This instrument designed for evaluate the performance of nursing students in clinical settings. Data were analyzed using descriptive and inferential statistics and SPSS software version 23. Results: After the intervention, scores showed three areas: professionalism (P <0.001), ethical principles (P <0.001), nursing process (P <0.001), and in General Student performance in clinical settings (P <0.001) in the intervention group was significantly higher than the control group. The effect size of nurses’ performance evaluation was 3.33 (3.82, 2.86). Considering that the Cohen effect size of nursing students’ performance evaluation scores and its dimensions was more than 0.80, so the effect of the intervention in evaluating its effect on the studied variables was high. Conclusions: Given the importance of establishing appropriate professional communication between nursing students and the effect that Peer Assist Model (PAM) can have on improving the level of clinical education, using this model will improve students’ clinical performance at a broader level.